Comprehensive Security: The Opportunities and Challenges of Incorporating Environmental Threats in Security Policy - Räisänen, Helmi (2021)
In security and foreign policy discourse, environmental issues have been discussed increasingly as security threats that require immediate action. Yet, as the traditional security sector does not provide straightforward means to deal with climate change and other environmental issues, this has prompted concerns over undue securitisation and ill-placed extreme measures. We argue that an effective policy to address foreseeable environmental security threats can only be developed and maintained by ensuring that it remains resolutely within the domain of civil society. In this article, we consider the case of Finland, where the policy concept of comprehensive security has been presented as the official guideline for security and preparedness activities in different sectors. Comprehensive security aims to safeguard the vital functions of society through cooperation between authorities, business operators, organisations, and citizens. We analyse the opportunities and challenges of Finland’s comprehensive security policy in addressing environmental changes through a three-level framework of local, geopolitical and structural security impacts. Our empirical evidence is based on a set of expert interviews (n = 40) that represent a wide range of fields relevant to unconventional security issues. We find that the Finnish comprehensive security model provides an example of a wide and inclusive perspective to security which would allow for taking into account environmental security concerns. However, due to major challenges in the implementation of the model, it does not fully incorporate the long-term, cross-sectoral, and cascading aspects of environmental threats. This weakens Finland’s preparedness against climate change which currently poses some of the most urgent environmental security problems.